2008
DOI: 10.1186/1471-2148-8-319
|View full text |Cite
|
Sign up to set email alerts
|

Sperm competition: linking form to function

Abstract: BackgroundUsing information from physics, biomechanics and evolutionary biology, we explore the implications of physical constraints on sperm performance, and review empirical evidence for links between sperm length and sperm competition (where two or more males compete to fertilise a female's eggs). A common theme in the literature on sperm competition is that selection for increased sperm performance in polyandrous species will favour the evolution of longer, and therefore faster swimming, sperm. This argume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
264
3
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(280 citation statements)
references
References 85 publications
10
264
3
3
Order By: Relevance
“…In some species, sperm length is positively associated with sperm's swimming velocity (for example, Mossman et al, 2009;Fitzpatrick et al, 2010), which may explain macroevolutionary patterns of sperm evolution, which suggest that species with relatively high levels of sperm competition produce longer sperm (Fitzpatrick et al, 2009;Tourmente et al, 2009). Despite these latter observations, however, the relationships between sperm length and sperm performance at the intraspecific level can be positive and negative (see Humphries et al, 2008), and some studies have shown that relatively short sperm can have a competitive advantage in sperm competition (Gage and Morrow, 2003;García-González and Simmons, 2007;Firman and Simmons, 2008). …”
Section: Introductionmentioning
confidence: 67%
“…In some species, sperm length is positively associated with sperm's swimming velocity (for example, Mossman et al, 2009;Fitzpatrick et al, 2010), which may explain macroevolutionary patterns of sperm evolution, which suggest that species with relatively high levels of sperm competition produce longer sperm (Fitzpatrick et al, 2009;Tourmente et al, 2009). Despite these latter observations, however, the relationships between sperm length and sperm performance at the intraspecific level can be positive and negative (see Humphries et al, 2008), and some studies have shown that relatively short sperm can have a competitive advantage in sperm competition (Gage and Morrow, 2003;García-González and Simmons, 2007;Firman and Simmons, 2008). …”
Section: Introductionmentioning
confidence: 67%
“…Studies on sperm dimensions have mainly focused on the benefits of increased length as a way of adapting to variations in the female reproductive tract. For instance, longer heads have been proven to positively influence fertility [61] while the general assumption is that longer sperm tails will increase the swimming potential of sperm [66,67]. Humphries et al [67], working on various animal species, came to the conclusion that, although there are a number of factors which may influence the swimming speed of sperm, the head:tail ratio provides a simple measurement to assess potential speed.…”
Section: Morphometrymentioning
confidence: 99%
“…The primitive filiform sperm is 'worm-like' in appearance and is also referred to as 'sauropsid' since it resembles reptilian sperm [37]. A degree of overlap between the two basic morphological sperm types has been observed, based mainly on the tendency towards spiralization seen in some non-passerine birds [67]. Sub-oscine species are also reported to display morphological features of both passerine and nonpasserine bird sperm [52].…”
Section: Sperm Structurementioning
confidence: 99%
“…Swimming velocity may also increase as a result of changes in the proportions between sperm components. A proportionately longer flagellum (in relation to sperm head size) may better overcome the drag of the sperm head (Humphries et al 2008, Tourmente et al 2011a.…”
Section: Introductionmentioning
confidence: 99%